2021
DOI: 10.1021/acsomega.1c01792
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Study of Water Injection Position and Pressure on the Knock, Combustion, and Emissions of a Direct Injection Gasoline Engine

Abstract: A turbocharged downsizing spark ignition (SI) engine combined with direct injection technology has the potential to improve the power and fuel economy and reduce emissions. However, gasoline engines are prone to knocking under low-speed and high-load conditions, which limits the application and development of downsizing SI engines. In this study, numerical simulation methods are used to explore the feasibility of water injection in the intake port to reduce the knock tendency of gasoline direct injection (GDI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The initial conditions and boundary conditions were calculated from experiments and 1D GT-Power software. 18 The initial conditions are shown in Table 4, and refer to the pressure, temperature, and other components. The boundary conditions mainly conclude: the piston top temperature is 565.9 K, the wall temperature of the combustion chamber is 565 K, the temperature of the spark plug is 1100 K, and the temperature parameters of other parts.…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial conditions and boundary conditions were calculated from experiments and 1D GT-Power software. 18 The initial conditions are shown in Table 4, and refer to the pressure, temperature, and other components. The boundary conditions mainly conclude: the piston top temperature is 565.9 K, the wall temperature of the combustion chamber is 565 K, the temperature of the spark plug is 1100 K, and the temperature parameters of other parts.…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%
“…The experimental conditions were from previous studies. 18 Figure 4 shows a comparison of experimental and numerical results on mean pressure and heat release rate (HRR). It can be seen from the figure that the simulation results of the mean pressure and HRR are well coupled with the experimental results, and the deviations are not more than 5%.…”
Section: Grid Independence and Numerical Model Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the pressure of PWI, Rocha et al 26 determined through experiments that water injection time and water injection pressure have a greater impact on fuel consumption when the IMEP is 8 bar than when the IMEP is 5 bar. Meanwhile, Li et al 27 found that the KI of the GDI engine was the lowest when the water injection pressure was set at 5 bar. During this time, the work cycle volume is the highest and the emissions of NO x and HC are the lowest.…”
Section: Introductionmentioning
confidence: 99%
“…The studies carried out focus on the injection of water in the intake manifold or creating an emulsion of water with the fuel injected, which shows the significant impact that the increase of water content has on the combustion efficiency and thus on the performance of the engine. This has been demonstrated with different kinds of thermal engines, such as gas turbines [64], diesel internal combustion engines [65]- [71], and petrol engines [66], [72]- [74]; obtaining the same result trend about the effect of the combustion air humidity on the performance and pollutant emissions of a thermal engine.…”
Section: Humiditymentioning
confidence: 84%